Freedom as the divine foundation of humannes. Fyodor Dostoevsky’s anthropological considerations - Perkowska, Iwona Magdalena (Hybris, 2013)
No doubt, freedom is the main topic in the works of Dostoevsky. There is probably no other artist and thinker who would say about freedom more - broadly and profoundly describing all its complexity. Freedom constitutes the humanity and at the same time it is the greatest threat to mankind. Man gets freedom as a gift from God, as a key element of his ontic structure. This gift can be a curse, the engine of destruction, ballast, which one need to quickly dump on someone's shoulders. According to Dostoevsky, a man bows his head humbly before the miracle, authority and wealth. He gives his freedom to those who will show him even a semblance of a miracle, will gain an advantage over him, or provide material prosperity. Freedom becomes ill when used arbitrary, enslaves the other, leads to violence and dehumanization.